Arabinofuranose‐derived positron‐emission tomography radiotracers for detection of pathogenic microorganisms. (28th March 2020) - Kalita, Mausam; Parker, Matthew F.L.; Luu, Justin M.; Stewart, Megan N.; Blecha, Joseph E.; VanBrocklin, Henry F.; Evans, Michael J.; Flavell, Robert R.; Rosenberg, Oren S.; Ohliger, Michael A.; Wilson, David M.
Abstract: PURPOSE: Detection of bacteria‐specific metabolism via positron emission tomography (PET) is an emerging strategy to image human pathogens, with dramatic implications for clinical practice. In silico and in vitro screening tools have recently been applied to this problem, with several monosaccharides including l ‐arabinose showing rapid accumulation in Escherichia coli and other organisms. Our goal for this study was to evaluate several synthetically viable arabinofuranose‐derived 18 F analogs for their incorporation into pathogenic bacteria. PROCEDURES: We synthesized four radiolabeled arabinofuranose‐derived sugars: 2‐deoxy‐2‐[ 18 F]fluoro‐arabinofuranoses (d ‐2‐ 18 F‐AF and l ‐2‐ 18 F‐AF) and 5‐deoxy‐5‐[ 18 F]fluoro‐arabinofuranoses (d ‐5‐ 18 F‐AF and l ‐5‐ 18 F‐AF). The arabinofuranoses were synthesized from 18 F ‐ via triflated, peracetylated precursors analogous to the most common radiosynthesis of 2‐deoxy‐2‐[ 18 F]fluoro‐d ‐glucose ([ 18 F]FDG). These radiotracers were screened for their uptake into E. coli and Staphylococcus aureus . Subsequently, the sensitivity of d ‐2‐ 18 F‐AF and l ‐2‐ 18 F‐AF to key human pathogens was investigated in vitro. RESULTS: All 18 F radiotracer targets were synthesized in high radiochemical purity. In the screening study, d ‐2‐ 18 F‐AF and l ‐2‐ 18 F‐AF showed greater accumulation in E. coli than in S. aureus . When evaluated in a panel of pathologic microorganisms, both d ‐2‐ 18 F‐AF and l ‐2‐ 18 F‐AF demonstrated sensitivity to most gram‐positive and gram‐negative bacteria. CONCLUSIONS: Arabinofuranose‐derived 18 F PET radiotracers can be synthesized with high radiochemical purity. Our study showed absence of bacterial accumulation for 5‐substitued analogs, a finding that may have mechanistic implications for related tracers. Both d ‐2‐ 18 F‐AF and l ‐2‐ 18 F‐AF showed sensitivity to most gram‐negative and gram‐positive organisms. Future in vivo studies will evaluate the diagnostic accuracy of these radiotracers in animal models of infection. Abstract : The unique metabolic requirements of bacteria motivated the development of four arabinofuranose‐derived radiotracers for positron emission tomography. These radiotracers were synthesized via triflated, peracetylated precursors and screened for their uptake in a panel of pathogenic bacteria. Several bacteria showed significant accumulation highlighting potential roles of these probes in detecting infection and other human diseases.